Gender differences in emergency medicine standardized letters of evaluation. Issue 2 (27th April 2022) - Mannix, Alexandra; Monteiro, Sandra; Miller, Danielle; Parsons, Melissa; Alvarez, Al'ai; Krzyzaniak, Sara M.; Gore, Katarzyna; Eraso, Daniel; Davenport, Dayle; Chan, Teresa M.; Gottlieb, Michael
Abstract: Objectives: The Standardized Letter of Evaluation (SLOE) is a vital portion of any medical student's emergency medicine (EM) residency application. Prior literature suggests gender bias in EM SLOE comparative ranking, but there is limited understanding of the impact of gender on other SLOE components. The study objective was to evaluate the presence of gender differences in the 7 Qualifications for EM (7QEM), Global Assessment (GA), and anticipated Rank List (RL) position. A secondary objective was to evaluate the gender differences in 7QEM scores and their link to GA and anticipated RL position. Methods: We performed a cross‐sectional study using SLOEs from a subset of United States applicants to three EM residency programs during the 2019–2020 application cycle. We collected self‐reported demographics, 7QEM scores, GA, and anticipated RL position. We utilized linear regression analyses and repeated measures ANOVA to evaluate if the relationship between the 7QEM scores, GA score, and anticipated RL position was different for men and women. Results: 2103 unique applicants were included (38.6% women, 61.4% men), with 4952 SLOEs meeting inclusion criteria. The average QEM (2.51 vs. 2.39; p  < 0.001), GA (2.68 vs. 2.48; p  < 0.001), and RL (2.68 vs. 2.47; p  < 0.001) scores were statistically higher for women than men. When exploring the relationship between the 7QEM and GA, Ability to communicate a caring nature to patients was not found to be a statistically significant predictor for men, but it was for women. When exploring the relationship between 7QEM and RL, Commitment to EM was not a significant predictor for men, but it was for women. Conclusions: Women scored higher than men on the 7QEM, GA, and anticipated RL position on SLOEs. The 7QEM scores factored differently for men and women.